Doing the New Tax History - Heaman, E. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
A response to remarks on Tax, Order, and Good Government at a C.H.A. roundtable. A defence of the argument that, historically, racism has delivered tax cuts and a reflection on the historiographical consequences of such a claim in an age of racism and tax cuts.